The role of confounding in the association between pregnancy complications and subsequent preterm birth: a cohort study. (30th November 2021) - Dunne, J; Tessema, GA; Pereira, G
Abstract : Objective: To estimate the degree of confounding necessary to explain the associations between complications in a first pregnancy and the subsequent risk of preterm birth. Design: Population‐based cohort study. Setting: Western Australia. Population: Women ( n = 125 473) who gave birth to their first and second singleton children between 1998 and 2015. Main outcome measures: Relative risk (RR) of a subsequent preterm birth (<37 weeks of gestation) with complications of pre‐eclampsia, placental abruption, small‐for‐gestational age and perinatal death (stillbirth and neonatal death within 28 days of birth). We derived e ‐values to determine the minimum strength of association for an unmeasured confounding factor to explain away an observed association. Results: Complications in a first pregnancy were associated with an increased risk of a subsequent preterm birth. Relative risks were significantly higher when the complication was recurrent, with the exception of first‐term perinatal death. The association with subsequent preterm birth was strongest when pre‐eclampsia was recurrent. The risk of subsequent preterm birth with pre‐eclampsia was 11.87 (95% CI 9.52–14.79) times higher after a first term birth with pre‐eclampsia, and 64.04 (95% CI 53.58–76.55) times higher after a preterm first birth with pre‐eclampsia, than an uncomplicated term birth. The e ‐values were 23.22 and 127.58, respectively. Conclusions: The strong associations between recurrent pre‐eclampsia, placental abruption and small‐for‐gestational age with preterm birth supports the hypothesis of shared underlying causes that persist from pregnancy to pregnancy. High e ‐values suggest that recurrent confounding is unlikely, as any such unmeasured confounding factor would have to be uncharacteristically large. Tweetable abstract: First pregnancy complications are associated with a higher risk of subsequent preterm birth, with evidence strongest for pregnancies complicated by pre‐eclampsia. Tweetable abstract: First pregnancy complications are associated with a higher risk of subsequent preterm birth, with evidence strongest for pregnancies complicated by pre‐eclampsia.